Rehabilitation therapies for older clients of the Ontario home care system: Regional variation and client-level predictors of service provision - Armstrong, Joshua J.; Zhu, Mu; Hirdes, John P.; Stolee, Paul (Disability and Rehabilitation, 2015)
Purpose: To examine regional variation in service provision and identify the client characteristics associated with occupational therapy (OT) and physiotherapy (PT) services for older adults in the Ontario Home Care System. Methods: Secondary analyses of a provincial database containing comprehensive assessments (RAI-HC) linked with service utilization data from every older long-stay home care client in the system between 2005 and 2010 (n = 299 262). Hierarchical logistic regression models were used to model the dependent variables of OT and PT service use within 90 d of the initial assessment. Results: Regional differences accounted for 9% of the variation in PT service provision and 20% of OT service provision. After controlling for the differences across regions, the most powerful predictors of service provision were identified for both OT and PT. The most highly associated client characteristics related to PT service provision were hip fracture, impairments in activities of daily living/instrumental activities of daily living, cerebrovascular accidents, and cognitive impairment. For OT, hazards in the home environment was the most powerful predictor of future service provision. Conclusions: Where a client lived was an important determinant of service provision in Ontario, raising the possibility of inequities in access to rehabilitation services. Health care planners and policy makers should review current practices and make adjustments to meet the increasing and changing needs for rehabilitation therapies of the aging population. Implications for Rehabilitation 1. For older adults in home care, the goal of rehabilitation therapy services is to allow individuals to maintain or improve physical functioning, quality of life and overall independence while living within their community. 2. Previous research has demonstrated that a large proportion of home care clients specifically identified as having rehabilitation potential do not receive it. 3. This article used clinical assessment data to identify the predictors of and barriers to rehabilitation services for older adults in the Ontario Home Care System. Barriers of PT included dementia diagnosis and French as a first language. Barriers to OT included dementia diagnosis. 4. Policies and practices related to service provision for older adults should be reconsidered if we are going to meet the demands of aging populations and increasing rates of functional and cognitive impairments.

Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains - de Moissac, Danielle; Giasson, Florette; Roch-Gagné, Margaux (Minorités linguistiques et société / Linguistic Minorities and Society, 2015)
Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En moyenne, 50 % des répondants disent demander des services en français, mais seulement 25 % affirment les recevoir. La pénurie de professionnels pouvant offrir des services en français est considérée comme la barrière principale à l’accès. L’offre active est essentielle et facilite la prestation des services dans la langue de choix de la clientèle. Mots-clés : accessibilité, santé, services sociaux, Manitoba, minorité francophone

Agir pour avoir accès à des services sociaux et de santé en français. Des francophones en situation minoritaire nous enseignent quoi faire! - Drolet, Marie; Arcand, Isabelle; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée (Revue canadienne de service social / Canadian Social Work Review, 2015)
Même si les droits des francophones de l’Ontario sont garantis par la Loi de 1986 sur les services en français, l’accès à des services sociaux et de santé en français dans cette province s’avère complexe en raison d’importantes barrières à recevoir de tels services sur un continuum. Nous avons exploré à l’aide d’entrevues qualitatives les points de vue de 40 parents et proches aidants francophones qui vivent en contexte bilingue dans la région d’Ottawa et dont l’enfant ou l’aîné pour lequel ils ont une responsabilité d’aidant utilise des services sociaux et de santé en français. Ces francophones s’avèrent des acteurs au sein de leur trajectoire de services, adoptant cinq stratégies pour accéder à de tels services. De plus, le sentiment de confort et la relation de confiance que procure l’usage du français tout au long de l’intervention, ainsi que le soutien des professionnels francophones ont facilité leur démarche. Il n’en demeure pas moins que l’offre de services en français ne doit pas devenir la responsabilité d’individus ou d’une minorité. Mots-clés : Francophonie en situation minoritaire, accès à des services sociaux, minorité linguistique, barrières aux services, offre active de services en français, entrevues qualitatives

Enjeux de santé des aînés francophones vivant en situation minoritaire : une analyse différenciée selon les sexes - van Kemenade, Solange; Bouchard, Louise; Bergeron, Christian (Reflets, 2015)
La recherche en santé sur les Communautés de langue officielle vivant en situation minoritaire révèle des disparités. Le fait d’être minoritaire dans une société, conjointement avec d’autres déterminants, comme le statut socioéconomique, l’éducation en santé, et le fait de ne pas avoir un soutien social contribuent aux disparités de santé. Dans le contexte du vieillissement plus marqué des populations de langue officielle vivant en situation minoritaire, nous avons examiné la situation des aînés francophones. Pour cela, une analyse secondaire des données issues de l’Enquête sur la santé des collectivités canadiennes (ESCC) a été réalisée. Nous présentons dans cet article, une analyse différenciée de leur situation sociosanitaire selon le sexe et le genre en dressant le portrait des états de santé, des incapacités et des besoins sur le plan des soins de santé. Mots-clés : aînés francophones, situation minoritaire, santé, accès aux soins, services de santé, sexe, langues officielles, Canada, Enquête de santé dans les collectivités canadiennes